Grand Design Pembinaan SDM Kearsipan di Lembaga Pendidikan Tinggi (Studi Dokumen Peraturan Kepala Arsip Nasional Republik Indonesia Nomor 12 Tahun 2017 Tentang Grand Design Pembinaan Sumber Daya Manusia Kearsipan) - Rahayuningsih, Fransisca (Ilmu Informasi Perpustakaan dan Kearsipan, 2020)
Law of Republic of Indonesia Number 43/2009 concerning archives mandates that the university archival implementation is the responsibility of the university itself. Therefor the preparation of competent human resource in archives is very important It is predicted that there are universities or higher education institutions that have not yet been fully considered the importance of archivist competency. This research aims to determine the grand design of developing competency on archival human resources. This research uses qualitative approach. The data resources used is The  Regulation of The Head  of Indonesian National Archives number 12 year of 2017 concerning the  grand design of archival human resources development. The grand design of archival human resources development includes archival human resources development strategy; the pattern and implementation of archival human resources development; performance and funding targets. The strategy of archival human resources development is held through improving performance management and improving the quality of archival human resources. The pattern of competency-based archival human resources development is implemented to develop integrated competency management from recruitment, selection, training dan development, assessment, remuneration, and career. Fostering process of archival human resources is carried out through the stages of planning, organizing, implementing and monitoring. ANRI construct the performance target of archiving human resources development which is measured and evaluated periodically at the end of the current year. The fund resource of archival human resources development comes from the state budget which is carried out in accordance with statutory provisions. Funding for developing archival human resources can also be done through financial support from local governments, state-owned business entities/local-owned business entities and state universities. The The urgency of this research is to find out a grand design of a systematic well-planned archival human resources development that having major impact on developing universities as an educational institution for young generation.